Effect of Soaking Comet Fish (Carassius auratus) larvae in Purwoceng Extract Solution on Growth and Percentage of Female Individuals - Abdullah, Nursanti; S Wibowo, Eko; Fabanjo, M. Abjan (Agrikan Jurnal Agribisnis Perikanan, 2021)
Comet fish (Carasius auratus) is one type of ornamental fish that is very popular with consumers and has commercial value because it has various shapes and colors such as yellow, white, black and red. Efforts to obtain the percentage of females can be done by sex transfer by immersing the larvae in purwoceng extract. Purwoceng extract (pimpinella alpina) is an aphrodisiac plant that contains compounds related to phytosteroids, such as stigmasterol which functions to improve sexual quality. This study used a completely randomized design with 4 treatments and 3 replications, the dose used was treatment A without dose (control), B dose 10 mg/l, C dose 15 mg/l, D dose 25 mg/l. The results showed that the highest percentage of female fish was present in the treatment dose (B) 10 mg of purwoceng extract, which was 45.94%, followed by treatment A 42.39%, treatment C 24.36%, treatment D 10.83%. While the highest growth was found in treatment D, namely 1.115 g, followed by C 0.820 g, B, 0.910 and A 0.785.